2014
DOI: 10.4314/ejhs.v24i0.5s
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Socio-Demographic Factors for Perinatal Mortality in Developing Countries: A Subgroup Analysis of the National Surveys and Small Scale Studies

Abstract: BACKGROUND: Although the perinatal mortality in low income countries is about five-folds higher than in the high income countries, little is known about the association of socio-demographic factors with perinatal mortality. National and small scale studies so far reported have shown very contradictory results. The objective of this meta-analysis was to assess the association of perinatal mortality with selected sociodemographic factors. METHODS: A computer based literature search was conducted mainly in the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
1
9
0
1
Order By: Relevance
“…Living in rural areas can be a risk for pregnant women since quality health services and infrastructure are usually more accessible in urban centres. Similar to our study, the meta-analysis done on developing countries showed that perinatal mortality was significantly higher in rural areas [20]. In Tanzania, a demographic health survey which was conducted in 2010 found that both women living in urban areas as well as in rural areas have increased risk of perinatal death [21].…”
Section: District Of Residencesupporting
confidence: 83%
“…Living in rural areas can be a risk for pregnant women since quality health services and infrastructure are usually more accessible in urban centres. Similar to our study, the meta-analysis done on developing countries showed that perinatal mortality was significantly higher in rural areas [20]. In Tanzania, a demographic health survey which was conducted in 2010 found that both women living in urban areas as well as in rural areas have increased risk of perinatal death [21].…”
Section: District Of Residencesupporting
confidence: 83%
“…The high TFR among the rural and uneducated women might have contributed to the increased risk of maternal and perinatal mortality in this group of women as the national surveys have already demonstrated ( 13 – 15 ). Another article has also shown a high proportion of maternal and perinatal mortality among rural and uneducated women, specifically in Ethiopia and some other SSA countries ( 20 ). Furthermore, as shown in Figure 3 , the Pearson correlation coefficient (r) has demonstrated a positive and strong association of maternal mortality ratio (MMR) with the TFR in 45 African countries (r = 0.6; P < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…As the regression lines showed, it seems that every increased birth has been associated with increased risk of maternal and perinatal deaths. However, it should be noted that there are several socio-demographic and obstetric factors that could determine maternal and perinatal outcome ( 20 – 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Though previous studies from different countries found associations of socioeconomic conditions with early neonatal deaths [ 20 , 37 ], recent analyses from several other studies found that socioeconomic inequalities in neonatal mortality in low and middle-income countries are falling. The explanation that has been put forward for the reduction of these inequalities is that the ‘diminution of inequalities’ associated with maternal and neonatal health service utilization [ 38 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%